2021
DOI: 10.1089/tmr.2021.0022
|View full text |Cite
|
Sign up to set email alerts
|

Barriers for Telemedicine Use Among Nonusers at the Beginning of the Pandemic

Abstract: Telemedicine has garnered considerably more attention during the COVID-19 pandemic than in any time previously. However, before the beginning of the pandemic, many individuals had not accessed care in this manner. The purpose of this study was to understand the central reasons that individuals had not used telemedicine before the pandemic. Therefore, we conducted a convenience sample survey in March-April 2020, and 539 participants living in the United States answered questions about exploring their reasons fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…There are several possible explanations for this finding. For example, a recent study found that some individuals had concerns regarding the privacy and security of telemedicine visits [ 19 ]. Perhaps these concerns impacted perceptions of usefulness in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible explanations for this finding. For example, a recent study found that some individuals had concerns regarding the privacy and security of telemedicine visits [ 19 ]. Perhaps these concerns impacted perceptions of usefulness in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of each correlate with age, income, ethnicity, rural location, and educational level. 6,[76][77][78] For example, older age and ethnicity were found to significantly predict telehealth use, with older populations from underrepresented racial and ethnic groups adopting telehealth the least, specifically Black and Hispanic individuals >65 years of age. 79 These relationships are significantly intertwined with broader structural and social determinants of health, underscoring the importance of bringing a multilevel lens to telehealth adoption and use to reduce rather than widen disparities in access and outcomes.…”
Section: Patient Barriersmentioning
confidence: 99%
“…79 These relationships are significantly intertwined with broader structural and social determinants of health, underscoring the importance of bringing a multilevel lens to telehealth adoption and use to reduce rather than widen disparities in access and outcomes. 76,78,80…”
Section: Patient Barriersmentioning
confidence: 99%
“…Due to certain challenges of telemedicine peculiar to low-income and middle-income countries (LMICs), there are insufficient healthcare resources available and are yet unevenly distributed due to the rural–urban divide 22. LMICs are characterised by a wider gap between the high-income earners and low-income earners with the latter constituting the larger percentage of the population 23. The disparity in these challenges denies particular population’s access to telemedicine services based on income, ethnicity, literacy and others 24…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine has shown potential in salvaging the dwindling healthcare system in LMICs but faced certain challenges that may create new health inequalities especially based on income 23. The health system framework as proposed by WHO describes the entire system under of six core ‘building blocks’ namely service delivery; health workforce; health information systems; access to essential medicines; financing and leadership/governance 25.…”
Section: Introductionmentioning
confidence: 99%